Undergraduate Students’ Perception of E-feedback Practice during Online EFL Thesis Proposal Writing Coursework - Muzdalifah, Afni Febriani; Hapsari, Astri (JOALL (Journal of Applied Linguistics and Literature), 2024)
Although there have been a few studies on written e-feedback in EFL writing coursework, the research on students’ perception of e-feedback practice in online learning in Indonesia's higher education context is still underexplored. This study aims to investigate EFL undergraduate students’ perception of the lecturers’ e-feedback practice during online thesis proposal writing coursework. Two students from two different classes were willing to participate in in-depth interviews. A descriptive qualitative approach with thematic analysis was employed as the research method. The findings revealed three prominent themes on how the students perceive the lecturers’ e-feedback practices. The participants perceived that the lecturers’ e-feedback practice:  (1) scaffolded the participants to develop technical and conceptual writing skills, (2) supported the participants' personal and academic development, and (3) influenced the participants’ emotions. Students who initially felt unable to face online classes during the COVID-19 pandemic gradually got used to and overcame the feeling of being unable to take online courses. This study implies that the lecturers’ role in being thoughtful in delivering feedback to students is critical because e-feedback as a pedagogical practice influences students’ social and emotional learning process in writing their undergraduate thesis. Participants who initially felt unable to face online classes during the COVID-19 pandemic, in the end, finally succeeded in overcoming the feeling of not being able to take online courses for their undergraduate thesis writing because they were being scaffolded, supported, and influenced by the lecturers’ e-feedback practices during their online learning.